Real-time simulation of surgical cutting in haptic environments using computational vademecums - Quesada, Carlos; Alfaro, Icíar; González, David; Cueto, Elías; Chinesta, Francisco (Jornada de Jóvenes Investigadores del I3A, 2023)
A method for the real-time simulation of surgical cutting in haptic environments is presented. It relies on the use of computational vademecums, i.e. PGDbased, pre-computed meta-models, which allow the solution to be obtained at fast rates. An example for corneal surgery is provided.